A conceptual framework of differentiated food consumption: The case of northern Greece - Evangelia Karamani; Eleftherios Alamanos; Eirini Tzimitra Kalogianni (International Journal of Business Science & Applied Management (IJBSAM), 2020)
The study introduces a conceptual framework explaining consumer behaviour towards differentiated food (natural/traditional, organic, functional, and luxury foods). A sample of 400 participant drawn from Thessaloniki, northern Greece, was used in the study. The result of a regression analysis showed that health consciousness, environmental consciousness, consumer attitudes to exploring new tastes, quality, and consumers' eating habits influence consumer behaviour. The antecedents of consumer behaviour can inform food related policies developed by stakeholders involved in the supply chains of differentiated products.
Keywords: 650; consumer behaviour; differentiated foods; multiple regression; Greece